Development of adaptive structures incorporating MEMS devices to be used as reflectarrays or transmitarrays. Issue 4 (April 2014) - Latif, Saeed I.; Safari, Mojtaba; Shafai, Cyrus; Shafai, Lotfollah
ABSTRACT The concept of adaptive array antenna is presented, where the array can be switched between a reflectarray state and a transmitarray state. Several configurations are discussed including a basic geometry comprising of just a slotted ground plane with MEMS bridges over each slot and a slotted ground plane with square patches or rings on both sides of the ground plane. In the later cases, the slots on the ground plane need to be shorted when a reflectarray is desired; otherwise, the array will behave as a transmitarray. The detail unit cell study is discussed for each case for the performance of the array. Experimental study is presented to verify the concept. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:935–938, 2014